Optimizing of Blended Experiential Learning Model in The Implementation of Microteaching to Improve Teaching Skills for Pre-Service Teachers - Sudarman; Ratna Fitri Astuti; Riyo Riyadi; Noor Ellyawati (Jurnal Edutech Undiksha, 2023)
The problem of teaching microteaching and its application in schools during the COVID-19 pandemic is that it is done online, while teaching skills must be implemented in real life. This study analyzes the application of the blended experiential learning model and finds the impact of pedagogical skills on pre-service teachers’ application of their teaching skills. This study is using a participatory action research method in the form of an action-based inquiry study of the Stringer model. The participants were pre-service teachers who were taking microteaching courses, 35 male and 81 female students, 4 supervisors, and 4 student teachers. Quantitative data analysis will be carried out through descriptive statistical analysis. The results of the research on the application of the blended experiential learning model were well implemented; there was an increase in the ability of pedagogical skills, the development of student potential, and assessment skills. It is concluded that the application of this blended experiential learning model improves the ability of prospective teachers to master students, learn theory, implement curriculum, facilitate the development of student potential, learn evaluation skills, and take reflective action.